Nanoscale infrared spectroscopy reveals complex organic–mineral assemblages in asteroid Bennu - Mehmet Yesiltas; Andrew Dopilka; Robert Kostecki; Timothy D. Glotch; Paul Northrup (Proceedings of the National Academy of Sciences, 2026)
Asteroid Bennu preserves primitive material from the early solar system, and returned samples allow direct examination of how organics and minerals were assembled and altered. We applied nanoscale infrared spectroscopy together with Raman spectroscopy to the Bennu sample OREX-800066-3 to characterize chemical variability at ~20 nm scales. Analysis of nano-Fourier-transform infrared spectroscopy spectra identifies three recurring compositional domains; aliphatic-rich, carbonate-rich, and nitrogen-bearing organic-rich regions. Statistical evaluation shows that these domains are compositionally and spatially distinct at the nanoscale, with strong negative correlations between aliphatic signatures and both carbonates and N-bearing organics, and negligible correlation between carbonates and N-bearing organics. Organosulfur compounds are spatially restricted to carbonate-rich regions, indicating organic-sulfate interactions during late-stage brine evolution. Raman spectra indicate highly disordered, thermally minimally metamorphosed carbonaceous matter, consistent with preservation of labile functional groups. These results demonstrate that Bennu’s angular lithology (characterized by planar facets and sharp edges) is not chemically uniform and records heterogeneous aqueous alteration rather than pervasive uniform processing. N-bearing organic functional groups are widely preserved despite extensive alteration, and carbonate-rich areas show intimate nanoscale mixing of different carbonate species. The coexistence of distinct organic- and carbonate-rich domains suggests contributions from both primordial compositional diversity and subsequent rock–fluid interaction. Comparison with Ryugu samples highlights shared features but key differences in organic-carbonate associations and carbonate distributions. Overall, Bennu’s nanoscale heterogeneity provides constraints on organic preservation, carbonate formation, organic-sulfate chemistry, and parent-body evolution in volatile-rich early solar system materials.